Diagnostic difficulties in a patient with precocious puberty and short stature observed for Kabuki syndrome - Kwiatkowska, Magdalena; Mandecka, Anna; Kempińska, Wiktoria; Błaszczyk, Ewa; Gawlik-Starzyk, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Kabuki syndrome (KS) is a rare dysmorphic syndrome characterized by multiple congenital anomalies and developmental disorders. The presented patient, who was born with weight and length too small for gestational age, was found to have multiple co-occurring disorders, including endocrinopathy – low growth and true (central, gonadotropin-releasing hormone-dependent) precocious puberty. In order to inhibit premature puberty and improve the prognosis of final height, treatment with triptorelin was initiated at the age of eight years and continued for a further 5 years. Next-generation sequencing was performed, which revealed a variant of uncertain clinical significance, which made it impossible to unequivocally diagnose KS. In this article, we describe the long process of seeking a diagnosis for rare genetic diseases.